Sovereignty vs-a-vis survival: a critical discourse analysis of the BBC and Al-Jazeera’s reporting on the Great Ethiopian Renaissance Dam negotiations - Biset Ayalew Nigatu; Yohannes Lijalem Lidetie (Cogent Arts & Humanities)
This research looked at news reports from the BBC and Al-Jazeera websites on the US-led negotiations on the Grand Ethiopian Renaissance Dam (GERD). Its objective is to investigate the ways the news stories of the BBC and Al-Jazeera covered the GERD issue. Two news stories were purposely selected from each medium just to show how ideology was embodied in the news texts. Critical Discourse Analysis (CDA) was used as a theoretical framework and research methodology. The findings indicate that news stories of the BBC and Al-Jazeera constructed GERD as a source of conflict and disagreement. Ethiopia was depicted as an aggressive social player, Sudan as passive, and Egypt as a GERD victim by the news stories of the BBC and Al-Jazeera. The GERD is also depicted as a confrontation between Ethiopian sovereignty and Egyptian survival. This depiction has ideological implications since it maintains the status quo or Egypt’s monopoly on the Nile, while demeaning Ethiopia’s and other upstream country’s rights to utilize the Nile.